Respon Pertumbuhan dan Biomassa Semai Rhizopora apiculata BI Terhadap Salinitas dan Kandungan Lipidanya pada Tingkat Pohon - Prayunita Prayunita; Mohammad Basyuni; Lollie Agustina (Program studi Kehutanan USU, 2012)
Growth and biomass Rhizopora apiculata BI seedlings under varied salinities and their lipid content at tree stage. The research was conducted at Green house, Faculty of Agriculture and Research Laboratory, Faculty of Pharmacy, University of North Sumatra from August 2011 to July 2012. This study aims to determine the effect of salinity on the growth and biomassa of mangrove non secreter R. apiculata seedlings level and lipid and NSL (Nonsaponifiable Lipids) content at tree level. Five levels of salinities of 0%, 0.5%, 1.5%, 2%, 3% were treated and seedlings were planted for 5 months. The results showed that maximum growth of R. apiculata seedling at 1.5% concentration, leaf number and leaf area were in the salinity of 0.5%. Stem and root biomass achieved in 1.5%, while the leaf biomass in the salinity of 0.5%. The content of total lipid and NSL obtained from the leaves and the roots R. apiculata tree. The content of total lipid R. apiculata trees in the leaves (9.60 mg) were more amounts than in the roots (6.40 mg). NSL content of R. apiculata trees in the roots (0,226 mg) were more than in the leaves (0.10 mg). The results of this study may provide information to the rehabilitation program in order to obtain R. apiculata seedlings growing best based on their salinities. Keywords : Mangrove, Rhizopora apiculata, Salinity, Morphology, Content of Lipid and NSL (Non Sapofiniable Lipid)